Nerve growth factor, neuropeptides and cutaneous nerves in atopic dermatitis - Hodeib Abeer; El-Samad Zeinab; Hanafy Hesham; El-Latief Amani; El-bendary Amal; Abu-Raya Azza (Wolters Kluwer Medknow Publications, 2010)
Introduction: Neurogenic components, as neurotrophic factors and neuropeptides, are probably involved in the pathogenesis of atopic dermatitis (AD) with the neuroimmunocutaneous system as they modify the functions of immunoactive cells in the skin. Nerve growth factor (NGF) is the best-characterized member of the neurotrophin family. Both NGF and neuropeptides (NPs) may be associated with the disease pathogenesis. Aim: This study aims to evaluate the plasma level of NGF and NPs in AD patients and correlate them with the disease activity and nerve changes in the skin by electron microscopy. Materials and Methods: Plasma levels of NGF and vasoactive intestinal peptide (+VIP) were measured by an immunoenzymatic assay while plasma levels of calcitonine gene related peptide (CGRP) and neuropeptide Y (NPY) were measured by radioimmunoassay in 30 AD patients in comparison to 10 normal non-atopic controls. Electron microscopic study was done in 10 AD patients. Results: It has been found that there is significant increase of plasma levels of NGF and NPs in AD patients compared with controls. There is a positive correlation between the plasma levels of NGF and disease activity (correlation coefficient = 0.750, P< 0.005). There is a significant correlation between the number of Schwann axon complex, evidenced by electron microscopic examination and plasma level of NGF in AD patients. Conclusion: It has been concluded that these neurogenic factors; NGF and NPs modulate the allergic response in AD, probably through interactions with cells of the immune-inflammatory component. NGF might be considered as a marker of the disease activity.